皮肤癣菌病和STAT3突变. (17th September 2018) - Simpson, J.K.; Fröbel, P.; Seneviratne, S.L.; Brown, M.; Lowe, D.M.; Grimbacher, B.; Fliegauf, M.; Fearfield, L.
Abstract : Linked Article:  Simpson et al. Br J Dermatol 2018;179 :750–754